Миграционные процессы и вопросы культурного взаимодействия в Закавказье в XII-VI ты с . до н.э. - Манько, Валерий; Чхатарашвили, Гурам (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Authors propose a new model of Neolithization of Transcaucasia. The transition to the Neolithic way of life was prepared by a series of population migrations from the territory of the Near and Middle East. Those migrations did not occur in the Neolithic, but at the end of the Plestocene and at the beginning of the Holocene, that is, on the eve of the Neolithic. The immigrants, apparently, sought to continue the development of traditional forms of economy in new territories. Such migrations are associated with the relocation of carriers of cultural traditions of Zarzian, Trialetian, M’lefaatian and Chayonu. The immigrants did not lose ties with their mother territories, which eventually led to the spread of Neolithic innovations in material culture and economy. Almost all migrant industries have become the basis for the formation of Neolithic cultures in Transcaucasia. The Zarzian migration occurred at the end of the Pleistocene and opened the way for the Trialetian migration of the late X-IX millennium BC. On the basis of the Trialetia complexes, the Chokh culture was formed. The migration of the M’lefaatian population led to the emergence of the Kobuleti industry. It became the basis for the Odishi Neolithic culture. The migration of carriers of Chayonu traditions led to the emergence of Neolithic cultures in Armenia. Thus, at the end of the Pleistocene and at the beginning of the Holocene, we observe large-scale migrations. The development of the Neolithic is accompanied by diffusion processes of small population groups, which carry out shuttle movements between Transcaucasia and the starting points of migration. These movements of small groups of the population ensured the creation of a single information space within which Neolithic innovations spread.
Keywords: Археология